Spectroscopic Identification of Diphosphene HPPH and Isomeric Diphosphinyldene PPH2 - Lu, Bo; Wang, Lina; Jiang, Xin; Rauhut, Guntram; Zeng, Xiaoqing (Angewandte Chemie International Edition, 2023)
The simplest diphosphene HPPH and isomeric diphosphinyldene PPH2 features prototype phosphorus‐phosphorus multiple bonding properties that have been of long‐standing interest in main‐group chemistry. Herein, we report the observation of cis‐HPPH, trans‐HPPH, and PPH2 among the respective laser photolysis products of phosphine (PH3) and diphosphine (P2H4) in solid N2‐ and Ar‐matrices at 10 K. The identification of these P2H2 isomers with matrix‐isolation IR and UV/Vis spectroscopy is supported by D‐isotope labeling and the quantum chemical calculations at the CCSD(T)‐F12a/cc‐pVTZ‐F12 level using configuration‐selective vibrational configuration interaction theory (VCI). Bonding analyses suggest that the two conformers of HPPH contain standard PP double bonds, whereas, PPH2 resembles P2 in having partial PP triple bond due to the H2P←P π bonding interaction. The simplest diphosphene HPPH (cis and trans conformers) and diphosphinyldene PPH2 have been generated and spectroscopically characterized in solid N2‐ and Ar‐matrices at 10 K. In addition to the photo‐induced conversion of these P2H2 isomers, the prototype phosphorus‐phosphorus multiple bonding properties have been disclosed.